PRODUKTIVITAS TENAGA KERJA PEREMPUAN PADA PANEN DAN PASCAPANEN TANAMAN KOPI (STUDI KASUS DI DESA PENINJOAN KABUPATEN BANGLI) - Handayani, M.Th.; Komala Dewi, Ratna (PIRAMIDA; Vol. 2, No. 2 Desember 2006, 2012)
The development of industry, agricultural sector, and other productive sector has to be increased and aimed to give a maximum economic growth. The productivity of agricultural sector has to be increased continuously, in order to increase the income and society welfare. In the coffe farming, especiallyin harvest and post harvest activities done by woman labor. Therefore it is to be considered to analyse their productivity. The objective of this study is find out (1) the productivity of woman labor in harvest and post harvest activities, and (2) the factors influential the activities. The study was conducted in The Village of Peninjoan. The District of Bangli. The location of study was chosen purposively. The number of sample is 30 which taken purposively. Collected data was analysed descriptively as well as using multiple linesr regression (SPSS). The result of this study, found that (1) the productivity of woman labor in harvest and post harvest of coffe plant was Rp.1,857.74 for hour, labor utilization average was 173.76 hour/season, and wage was Rp 323,533.00/season, and (2) the influence factors to the productivity of woman labor in harvest and post harvest of coffe plant are the experience of farmers, labor utilization, wage, and age. It is suggested that the wages of woman and man labor should be equal, so that there is no biased.
Keywords: productivity, woman labor, harvest, coffe plant